Females and post-pubescent adolescents: groups with high exposure to the development of body image dissatisfaction in São Bonifácio, Santa Catarina State, Brazil - Yara Lucy Fidelix; Edio Luiz Petroski; Andreia Pelegrini (Acta Scientiarum. Health Sciences, 2014)
To determine the prevalence of body image dissatisfaction in adolescents and analyse associated factors. The sample under analysis comprised 278 adolescents, 10- to 17-year-old students from government schools in a small town in southern Brazil. Sociodemographic information was collected (age, sex, area of residence and educational level of family head), coupled to self-assessment of sexual maturation and body image perception (scale of body silhouettes). Frequency distribution was employed for statistical analysis; Student’s t test was applied for independent samples; chi-square and Fisher's exact test and Poisson regression with robust variance adjustment were used. The prevalence of body image dissatisfaction was 59.3%, or rather, higher among females (65.6%) than among males (53%). An association between body image and sexual maturation existed which revealed that post-pubescent adolescents were more likely to show body image dissatisfaction when compared to their pre-pubescent peers. Females and post-pubescent adolescents were more likely to feel body image dissatisfaction. Intervention programs may be proposed as strategies for the construction of a positive body image.